Modelling the Effects of Public Support to Small Firms in the UK - Paradise Gained? - Mark Hart; Stephen Roper (European Regional Science Association (ERSA), 2003)
The evaluation of the impact of public policies to improve the performance of the small business sector has provoked a great deal of debate and research activity in recent years. The debate can be categorised in two broad ways. First, it can be seen in terms of the actual impact measures and schemes of small business support may have in terms of enhanced growth performance of SMEs. Second, the search for appropriate evaluation methodologies which reflect the range of problems associated with the accurate identification of the true effects of policy support. The much publicised "Six Steps to Heaven" paper by Storey (1998) provided a comprehensive overview of the problems associated with evaluation studies in the realm of the small business sector. Storey argued that the vast majority of assessments of the impact of policy support fall within the category of monitoring rather than true evaluation. The intention in this paper is to undertake an evaluation of Business Links in England adopting a methodology which seeks to avoid the methodological pitfalls articulated by Storey and in so doing achieve the approach. This paper describes the methodology employed in a tracker study of businesses that received advice and consultancy from the Business Link network in 1996. The purpose of the study was to assess the impact of Business Link support on productivity compared to a matched comparison group. Using data from the specially constructed Business Link Impact Indicators Database for the period 1994-2000 together with a survey of assisted firms and non-assisted firms, and adopting an econometric approach designed to make allowance for both 'assistance' and 'selection' effects, this study concludes that: · First, we find no evidence that in 1996 BL assistance was being targeted effectively at faster growing firms. · Second, we find some, albeit tentative evidence, that BL assistance in 1996 was having a positive effect on productivity growth. · Third, we identify a positive but statistically insignificant effect of BL assistance on turnover and employment growth. · Fourth, our analysis has highlighted a number of other factors which contribute to productivity, turnover and employment growth. The range of these factors - embracing market conditions, business strategy, the characteristics of the owner-manager and the firm itself - emphasise the complexity of the process of business growth and the consequent difficulties in both modelling and assisting the process.
Keywords: 330